Life cycle assessment of a renewable energy generation system with a vanadium redox flow battery in a NZEB household - J. R. Gouveia; E. Silva; T. M. Mata; A. Mendes; N. S. Caetano; A. A. Martins (Energy Reports, 2020)
Buildings are responsible for a significant part of the global energy consumption. Besides the need to improve their energy efficiency, new buildings also need to generate their own energy, preferably from renewable sources, to become more sustainable. As renewable energy generation is strongly dependent on the climatic conditions, energy storage must be considered when designing such a system. In this study, a cradle-to-grave life cycle assessment (LCA) study of a renewable energy generation system with a prototype Vanadium flow battery integrated in a Near Zero Energy Building (NZEB) is performed. A combined grid-connected PV and a solar thermal system generates the energy, and it was dimensioned to supply the annual energy needs of a household in Porto, Portugal considering the local climatic conditions. As an end of life scenario, it is assumed that the battery is dismantled and most of the materials are recycled. A functional unit of 1 kWh of supplied energy to the system was considered, and study results show that environmental impacts are reduced when the energy is produced onsite and the battery components are recycled or reused. A sensitivity analysis was conducted changing the household's geographic location.
Additional information: A joint organization of University of Aveiro (UA), School of Engineering of the Polytechnic of Porto (ISEP) and SCIence and Engineering Institute (SCIEI). - The 6th International Conference on Energy and Environment Research, July 22-25, 2019, University of Aveiro, Portugal.
Keywords: 330; Energy storage systems; Life cycle assessment; Near zero energy buildings -~NZEB; Vanadium redox flow battery